Photothrombosis of Corneal Neovascularization by Photodynamic Therapy Utilizing Verteporfin and Diode Laser - Hassan, Aziza Ahmed; Ghoneim, Dina Foad; EL-Dib, Amr; Abdelkawi, Salwa Ahmed; Abdel-salam, Ahmed Medhat (Journal of Lasers in Medical Sciences, 2013)
Introduction: The aim of the present study was to evaluate the effect of photodynamic therapy in the treatment of experimental corneal neovascularization (NV) with benzoporphyrin derivative (BPD). Methods: One group was considered as control (n=6 eyes) then, corneal NV was induced in 30 New Zealand male rabbits (n=60 eyes) by placing 7.0 silk sutures at midstromal depth approximately1mm from the limbus. Fifteen rabbits with corneal NV were left without any treatment, and 15 rabbits were subjected to photodynamic therapy (PDT) by intravenous injection with Verteporfin at a dose of 1.5 mg /Kg. Diode laser (660 nm) was applied after 15minutes for 5 minutes with a power of 50 mW/cm2. All rabbits were successively followed up by slit lamp examination for periods of 1 day, 1, 2, 3 and 4 weeks. Three rabbits were selected and sacrificed weekly (n=6 eyes each) and the corneas were isolated for histopathological examination. Results: The results of slit lamp examination indicated the gradual regression of the cornea neovascularization 4 weeks of PDT. Furthermore, regression of corneal neovascularization was documented clinically by decrease number and length of blood vessels and by histopathological examination. Conclusion: PDT with Verteporfin can provide efficacious treatment of corneal neovascularization.